English medieval misericords : the margins of meaning - Hardwick, Paul (Boydell studies in medieval art and architecture, 2011)
Introduction: What lies beneath -- A fair field of folk -- Doctrine and debate -- Influence and invention -- Masculinity and power -- Exemplary animals -- The monsters at the margins -- Conclusion: looking both ways.